Corporate social responsibility regulation in capital market and environmental information disclosure of listed companies: A quasi-natural experiment from China - Zhang, Changjiang; Zhang, Yue; Zhang, Sihan; Hou, Mengxiao; Chen, Yuqing (Frontiers in Environmental Science, 2022)
Based on a quasi-natural experiment generated by the Shenzhen Stock Exchange (SZSE) of China, which issued the Guidance for Social Responsibility of Listed Companies (referred to as Guidance) in 2006, this paper utilizes a panel dataset of A-share listed companies at Shanghai Stock Exchange (SSE) and SZSE from 2004 to 2008, and employ difference-in-differences (DID) method to investigate impact of the Guidance on environmental information disclosure quality (Eidq) of listed companies. The finding shows that exchange’s corporate social responsibility (CSR) regulation contributes to improving the Eidq of listed companies. Furthermore, policy effects of the Guidance are more significant in eastern region, heavily polluting industries and state-owned enterprises (SOEs). This study provides theoretical evidence and policy implications for the “two-wheel drive” of China’s stock market regulation and social supervision, and for the construction of an environmental information disclosure system that is more targeted in terms of region, industry and property rights, and that effectively promotes fulfillment of environmental governance responsibility by listed companies and guides their sustainable development actions.